SmarTasko: Supporting short and spontaneous activities of daily living of ADHD individuals - Moroyoqui, Marcos; Espina, David; Osuna, Hector; Escobedo Bravo, Lizbeth Olivia (My University, 2022)
The ability to complete Activities of Daily Living (ADL) might be hindered by external stimuli. This problem becomes harder for ADHD individuals since it is easier to postpone or forget activities and keep track of multiple activities at the same time. To maximize the ADL completion rate, while minimizing the number of intrusive stimuli, in this research we proposed SmarTasko, an activity-tracking wearable system focused on simplifying the interaction between the user and the device, making ADL tracking less obtrusive and habit forming. We interviewed 10 individuals, among neurotypical and ADHD individuals, to learn about the challenges when dealing with multiple short and spontaneous activities at the same time. We proposed two contributions from this research, a set of five design principles we have learned from our user-centered study, and the design of SmarTasko.
ACM DIGITAL LIBRARY
Keywords: Supporting short; ADHD individuals; Campus Tijuana